Are children with unilateral hearing loss more tired?. (April 2022) - Carpenter, Delaney; Dougherty, William; Sindhar, Sampat; Friesen, Tzzy-Nong; Lieu, Judith; Kesser, Bradley W.
Abstract: Objective: To determine whether children with unilateral sensorineural hearing loss (USNHL) and unilateral conductive hearing loss (UCHL) have higher levels of fatigue than literature reported normal hearing (LRNH) children. Methods: This was a cross-sectional survey utilizing the PedsQL™ Multidimensional Fatigue Scale administered to children with unilateral hearing loss (UHL) and their parents at two tertiary care academic medical centers and a nationwide microtia/atresia conference. The PedsQL™ Multidimensional Fatigue Scale was used to compare child and parental proxy reports of fatigue among USNHL, UCHL, and LRNH children. ANOVA and post-hoc Tukey Honest Significant Difference testing were used for statistical analysis. Results: Of 69 children included in the study, 42 had UCHL (61%) and 27 (39%) had USNHL. Children with USNHL reported more total fatigue (mean 69.1, SD 19.3) than LRNH children (mean 80.5, SD 13.3; difference −11.4; 95% CI: −19.98 to −2.84) and children with UCHL (mean 78.0, SD 14.5; difference −8.95; 95% CI: −17.86 to 0.04). Children with UCHL reported similar levels of fatigue compared to LRNH children (difference −2.5; 95% CI: −9.95 to 5.03). Parents of children with USNHL reported greater levels of fatigue (mean 67.6, SD 22.6) in their children than parents of LRNH children (mean 89.6, SD 11.4; difference −22.0; 95% CI: −29.8 to −14.3) and parents of children with UCHL (mean 76.2, SD 17.3; difference −8.6; 95% CI: −17.5 to 0.21). Parents of children with UCHL also report higher levels of fatigue than parents of LRNH children (difference −13.4; 95% CI: −19.98 to −6.84). Conclusions: Children with USNHL reported greater levels of fatigue than LRNH children and children with UCHL. Results implicate cognitive load as an important consideration in children with hearing loss. The measurement of fatigue may be a useful indicator to determine the benefit of intervention (e.g., amplification) for these children.